How we break : navigating the wear and tear of living - Deary, Vincent (Deary, Vincent. How to live trilogy, 2024)
"Drawing on cutting-edge science and intimate personal stories, an essential and paradigm-shifting book for readers struggling with fatigue, burnout, stress, and trauma--and for all of us who sometimes feel like we have been pushed past our breaking point"--